Review of the genus Apiocephalus Gahan, 1898 (Coleoptera, Cerambycidae) with description of a new species - Guanglin Xie (ZooKeys)
Taxonomic notes on the genus Apiocephalus Gahan, 1898 are provided. The genus is newly recorded in China with the description of a new species, Apiocephalus yangmingae sp. nov., from the Qinling Mountains. Brief redescriptions of Apiocephalus punctipennis Gahan, 1898 and Apiocephalus licheneus Gahan, 1906 are presented, along with their holotype photographs. A key to the known species is given.